Chemistry of carbon nanostructures - Müllen, K. (Klaus); Feng, Xinliang (De Gruyter, 2017)
"Carbon Materials such as nanoparticles, fibres, adamantan- and graphene like structures are widely used in science and engineering. Applications range from energy and gas storage, to electronics and optical applications. The authors contributing to this book, worldwide known experts on graphene and carbon structures, discuss chemical aspects of carbon structures, their synthesis, functionallization and design strategies for defined applications"--